EFFICACY AND SAFETY OF INTRA-ORAL BUCCAL FAT PAD EXCISION FOR BILATERAL CHEEK SLIMMING (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the effectiveness and safety of buccal fat pad excision for bilateral cheek slimming.Subjects and methods: A prospective, uncontrolled, clinical intervention study on 38 patients who wanted to reduce cheek fullness bilaterally, were re-examined and evaluated at 1 week, 1 month and 3 month after the surgery at The Gioi Dep aesthetic surgery clinic, Ho Chi Minh city from January 2022 to September 2025. Efficacy was evaluated by the survey of patient satisfaction on a 10-point scale and post-operative volume consideration of buccal fat pad by ultrasonography at 3 months after surgery. Safety was assessed by recording all adverse events and reactions at each visit.Results: Patient satisfaction was relatively high with an average score of 8.5/10. The mean pre- and post-operative buccal fat pad volumes were 6.83 ± 0.40 mL and 4.84 ± 0.37 mL respectively. Only 4/38 patients experienced complications (10.53%). The most complication was heavy trismus in patients with severe swelling and pain, but this complication gradually subsided within an average of 10 days.Conclusion: Intra-oral buccal fad pad excision resulted in good bilateral cheek contouring with high patient satisfaction and low complication rate.
Keywords: Buccal fat pad, buccal fat pad excision.